2020
DOI: 10.3390/pharmaceutics12020097
|View full text |Cite
|
Sign up to set email alerts
|

Development of Meloxicam-Human Serum Albumin Nanoparticles for Nose-to-Brain Delivery via Application of a Quality by Design Approach

Abstract: The aim of this study was to optimize the formulation of meloxicam (MEL)-containing human serum albumin (HSA) nanoparticles for nose-to-brain via a quality by design (QbD) approach. Liquid and dried formulations of nanoparticles containing Tween 80 and without the surfactant were investigated. Various properties, such as the Z-average, zeta potential, encapsulation efficacy (EE), conjugation of MEL and HSA, physical stability, in vitro dissolution, in vitro permeability, and in vivo plasma and brain distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Liposomes as lipid-based nanoDDS with reduced particle size and the bilayer lipid membrane provided high and fast transport of encapsulated lamotrigine through the nasal mucosa [17]. The in vivo studies of meloxicam (MEL)-containing human serum albumin nanoparticles corroborated the in vitro dissolution and permeability studies contributed to determine the criteria of trans-epithelial and axonal transport ensuring higher cerebral concentration of the API [18]. These results gave the background of the investigation of polymeric micelles, which may offer more favorable pharmacokinetics and higher protection to the API.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Liposomes as lipid-based nanoDDS with reduced particle size and the bilayer lipid membrane provided high and fast transport of encapsulated lamotrigine through the nasal mucosa [17]. The in vivo studies of meloxicam (MEL)-containing human serum albumin nanoparticles corroborated the in vitro dissolution and permeability studies contributed to determine the criteria of trans-epithelial and axonal transport ensuring higher cerebral concentration of the API [18]. These results gave the background of the investigation of polymeric micelles, which may offer more favorable pharmacokinetics and higher protection to the API.…”
Section: Introductionmentioning
confidence: 90%
“…In vitro permeability study of MEL-loaded polymeric micelles in triplicate compared to crystalline MEL; data are means ± SD (n = 3 independent formulations). To estimate the statistical in vivo brain distribution of MEL-containing polymeric micelles IVIVC was performed applying in vitro and in vivo data of previous experiments, namely a MEL suspension, MEL-containing human serum albumin nanoparticles with Tween-20 (MEL-HAS-Tween) and without surfactant (MEL-HAS) [18] as well as a MEL-containing nanosuspension [27]. These formulations contained MEL in the same concentration.…”
Section: In Vitro Nasal Diffusion Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-inflammatory agents such as meloxicam (MEL) (Figure 8), a selective cyclooxygenase 2 (COX-2) inhibitor, are effective to neuroinflammation in AD. MEL-loaded albumin nanoparticles showed a higher cerebral concentration of MEL through intranasal administration in an in vivo assay using rats, compared to intravenous administration [55]. Thus, this system based on albumin-based nanoparticles can be applied for intranasal insulin delivery.…”
Section: Intranasal Administration Using Nanoparticlesmentioning
confidence: 90%
“…It is noteworthy that in this way the BBB is bypassed [ 1 , 31 ]. Therefore, molecular mass of the drug in this case is less important for the absorption process, and it has been reported that both small [ 32 , 33 ] and large molecules [ 34 , 35 ] can be successfully delivered in this way. However, despite numerous interesting features, there are also several drawbacks related to this administration route.…”
Section: Introductionmentioning
confidence: 99%